PENGEMBANGAN MEDIA AUDIO LAGU ANAK USIA 4-6 TAHUN DI LEMBAGA PAUD AN-NURR - Wulandari, Rina (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Teachers as one of the stimulators of music in children is supposed toprovide stimulation in accordance with the stages of childdevelopment. Related to this, the observations obtained in the field ofhuman resources issues that early childhood teachers in the field of artmusic in general, causing minimal experience obstacles whenintroducing the song in children. This study tries to answer questionsrelated to the field of media development need for the audio track ofchildren. The research approach using a model of developmentrecording music using cool edit pro from Purwacandra (2007). Theresult are audio media children song in the An-Nurr that according tochild development capabilities related to music.